Code Switching and Code Mixing Used by Students in An English Classroom - Moh. Fuadul Matin; Refi Ranto Rozak (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study examines the use of code mixing and code switching among university students during English classroom interaction. Using a descriptive qualitative design, data were collected from one English class consisting of 25 students through classroom observations, audio recordings, and interviews. The findings reveal three types of code switching (intersentential, intrasentential, and tag switching) and three types of code mixing (insertion, alternation, and congruent lexicalization). Students switched and mixed codes due to limited vocabulary, the need for clarification, classroom atmosphere, and peer solidarity. These practices served pedagogical, communicative, cognitive, and social functions. The study concludes that code switching and code mixing are natural bilingual strategies that support understanding and classroom engagement. Teachers are encouraged to apply strategic bilingual approaches to facilitate learning while promoting English proficiency.